Influence of Water Saturation Time on Microstructure and Mechanical Properties of Jointed Limestone - Li, Huigui; Wang, Jun; Wang, Xiaohe; Liang, Wanliang; Xu, Guosheng; Kang, Yingchun (Frontiers in Earth Science, 2022)
In order to study the influence of water saturation time on the mechanical properties of jointed limestone, the joint limestone samples with a crack length of 20 mm and a crack angle of 30° are saturated with water for 0 day, 1 day, 3 days, 5 days and 7 days and tested with the RMT-150C mechanical test machine. The research results show that the water saturation time has a significant effect on the stress-strain curve, peak strength, elastic modulus, crack development and failure characteristics of the jointed limestone. There is a step rise or fall phenomenon near the peak stress. The peak strength and elastic modulus of the joint limestone are significantly negatively correlated with the saturated time. Compared with that of the saturated 0-day sample, the peak compressive strength of the saturated 1-day, 3-day, 5-day and 7-day samples was decreases by 16.5%, 24.7%, 43.6%, and 47.7%, respectively, and the elastic modulus decreases by 11.0%, 32.0%, 45.0%, and 67.9%, respectively. Saturated water cracks the skeleton particles of the limestone samples, and the length of the microscopic pores and fissures increases gradually. The phenomenon that the number and length of cracks increase with the increase of the water saturation time will weaken the mechanical properties of the jointed limestone. The physical and chemical reactions, lubrication, and pore water pressure produced by water-saturated water-rock interactions make it easier for the Mohr stress circle to reach the limit equilibrium state. Saturated water reduces the degree of fragmentation of the sample, and the integrity of the fracture surface is higher after failure. The findings in this paper are helpful to further reveal the mechanism of the crushing of supports and the frequent occurrence of water gushing accidents at the working face in the Xinhua region of northwestern Guizhou.